(3TQM GdaUhUs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3hHYO GdYbhd GdSdjeI hGdWHGY GdeSJbjeI s
(3BNQgG (B:s
(3dg bOQI JGeI Ydi EYOGe GdYOe jYfi CehQ dG JSJMb GdhLhO s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs